The teaching of philosophy in Spain: results and prospects (Journal of Parents and Teachers, 2012)
Significant changes have ocurred in the education of philosophy in Spain, in recet decades. The plan of study in secondary education not always count with philosophy as a subject, while in universities are offreing, more and more, philosophy as a degree. Now, it’s even posible to find philosophy for children in primary education. All this raises challenges and, also, show us the need of formulate proposals that promote this discipline to improve the integral training of people.
Keywords: Teaching philosophy; Education in Spain; critical thinking; Philosophy for children; Bachillerato; Primary education; Secondary education; Philosophy degree.; opinion